Layout of Laminated Bus Bar for Diode Neutral Point Clamped Three-level Inverter (Kongzhi Yu Xinxi Jishu)
Based on the design requirements of low inductance for diode neutral point clamped(NPC) inverter, it analyzed forced commutation operation modes of the inverter’s main circuit, described a layout theory of low inductance laminated bus bar and presented 3 layout schemes. In order to access the optimum design, the merits and demerits of the schemes were compared and analyzed by simulation.